Study on dynamic instability characteristics of functionally graded material sandwich conical shells with arbitrary boundary conditions. (April 2021) - Fu, Tao; Wu, Xing; Xiao, Zhengming; Chen, Zhaobo
Highlights: Dynamic instability of sandwich conical shell with arbitrary boundary condition is studied. The boundary conditions are implemented by using the artificial spring boundary. Basic equations are derived using first order shear deformation theory (FSDT). GDQ and Bolotin methods are utilized to obtain the principal instability regions. The effects of various parameters on the dynamic instability regions are investigated. Abstract: This paper presents analytical studies on the dynamic instability of functionally graded material (FGM) sandwich conical shell subjected to time dependent periodic parametric axial and lateral load. In the analysis, four kinds of sandwich distributions, including FGM core and isotropic skins, and isotropic core and FGM skins are considered and the power law distribution is employed to estimate the volume of the constituents. The arbitrary boundary conditions of the FGM sandwich conical shell are achieved by using the artificial spring boundary. The governing equations of conical shell subjected to parametric excitation are established by the Hamilton's principle considering first order shear deformation shell theory. Then the Mathieu-Hill equations describing the parametric stability of conical shell are obtained by generalized differential quadrature (GDQ) method, and the Bolotin's method is utilized to obtain the first-order approximations of principal instability regions of shell structure. By comparing the numerical results with the existing solutions in open literature, the validity of the proposed theoretical model is verified. Finally, the influences of sandwich distribution types, gradient indexes, skin-core-skin ratio and load forms on the dynamic stability of FGM sandwich conical shell have been investigated.